PERAN BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS SISWA DI SDN 1 BUJUR TENGAH, PAMEKASAN - Kurnia Nofita Rahmawati, Roro; Fithriyah, Imaniyatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the gap between the mandate of Child-Friendly Schools (CFS), which emphasizes holistic well-being, and the implementation of Guidance and Counseling (GC) services in elementary schools, which often remains limited to disciplinary and curative functions. The research aims to analyze the actual role of GC services in enhancing students' psychological well-being at SDN 1 Bujur Tengah Pamekasan, explore multi-stakeholder perceptions, and formulate an integrated model. Employing a qualitative case study approach, data were collected through in-depth interviews with GC teachers, principals, classroom teachers, and students, participant observation, and document analysis. The findings reveal three critical points: first, a dichotomy exists between the ideal GC program structure and daily practices dominated by reactive case handling, thereby neglecting developmental services for all students. Second, perceptions of GC remain fragmented and stigmatized; teachers view its impact casuistically, while student access is limited and often associated with rule-breaking. Third, collaboration between GC teachers and subject teachers occurs incidentally without institutionalized systemic support. The study concludes that GC has not yet functioned optimally as an architect of students' psychological well-being and recommends a Networked GC Model within the CFS Ecosystem. This model emphasizes restructuring programs toward promotive-preventive approaches, strengthening collaboration through formal forums and instruments, and building partnerships with parents to create cohesive systemic support for the well-being of the entire school community.